ANALISIS EFEKTIVITAS KARTU ELECTRONIC TOLL (E-TOLL) PADA PT. JASA MARGA TBK. CABANG BELMERA - Diah Permata Sari; Muhammad Asnawi; Rani Rahim (Universitas Dharmawangsa, 2022)
An electronic toll card (e-toll) is an electronic card used to pay toll road entrance fees in some parts of Indonesia. E-toll card users only need to paste the card to pay tolls in 4 seconds, faster than paying in cash which takes 7 seconds. This study aims to analyze the effectiveness of the electronic toll (e-toll) card and determine the constraints on the effectiveness of the electronic toll (e-toll) card at PT. Jasa Marga Tbk. Belmera Branch. The research method used is qualitative research. The result of this research is the effectiveness of the electronic toll card at PT. Jasa Marga Tbk. The Belmera branch has been effective as having a good understanding of the electronic toll card program, in implementing the electronic toll card program it has been right on target in accordance with its target, namely the implementation of cashless and has provided time efficiency that makes it easier for the public to access toll roads in the range of 1-5 seconds, although not 100% but it is very good where people have transacted using electronic toll cards in accessing toll roads in Medan City, it has provided real changes in the form of no queues of congestion at exit gates, for companies the HR burden is reduced and more efficient in operation, for people are getting used and educated in the application of cashless, it is easier to detect the details of people's transactions, and is more time efficient.